Advancing systemic therapy for biliary tract cancer: current strategies and emerging paradigms - Choucair, Khalil; Chamseddine, Shadi; Azmi, Asfar; Philip, Philip A. (Frontiers in Oncology, 2026)
Most patients diagnosed with biliary tract cancer (BTC) present with advanced, often unresectable disease. Additionally, a significant proportion of those who undergo curative intent resection experience disease recurrence. The aggressive nature and poor prognosis of BTC underscore the urgent need for effective and safe systemic therapies. For many years, progress in the therapy of BTC was limited. However, advances in our understanding of the molecular biology of BTC created a paradigm shift in its treatment. Novel therapies, particularly personalized approaches based on genomic profiling and use of targeted treatments, have significantly transformed the management algorithm for advanced BTC. These advances represented a major step forward in improving outcomes for patients with this very challenging malignancy.